Information privacy practices in e‐government in an African least developing country, Rwanda. Issue 2 (29th January 2019) - Mutimukwe, Chantal; Kolkowska, Ella; Grönlund, Åke
Abstract: Privacy of information is a critical issue for e‐government development as lack of it negatively influences users' trust and adoption of e‐government. To earn user trust government organizations need to provide reliable privacy assurance by implementing adequate information privacy protection (IPP) practices. African least developing countries (LDCs) today develop e‐government, but focus is on quick technical development, and the status of IPP issues is not clear. Little research has yet studied the status of IPP practices in e‐government in African LDCs. To fill this gap, we assess the status of existing IPP practices in e‐government in Rwanda, using international privacy principles as an assessment baseline. We adopt a case study approach including three cases. Data were collected by interviews and a survey. The findings call into question the efficacy of existing IPP practices and their effect in ensuring e‐government service users' privacy protection in Rwanda. The study extends existing literature by providing insights related to privacy protection from an African LDC context. For practitioners in Rwanda and other LDCs, this study contributes to the protection of information privacy in e‐government by providing recommendations to mitigate identified gaps.